Identifikasi Potensi Komoditas Unggulan Sektor Peranian Tanaman Pangan. Jurnal Ilmiah Pertanian - Eka Handayani; Khairul Saleh; Ellen Panggabean (Universitas Medan Area, 2019)
The aim in this study were (i) determine the base region commodity crops in Deli Serdang, (ii) determine differences in the level of competitiveness of commodity crops in Deli Serdang, (iii) determine specialty crops in the district of Deli Serdang, (iv) knowing localization (deployment) crops in Deli Serdang, (v) to determine the trend of food crops in Deli Serdang. The analytical method used is: (a) analysis of location quotient (LQ), (b) Shift Share analysis, (c) the analysis of the coefficient of specialization, (d) analysis of localization, (e) the analysis of the trend. Characteristics deployment commodity crops in Deli Serdang regency does not lead to the principle of specialization and localization. Patterns of production on food crops in Deli Serdang district tends to spread in many regions or districts and no commodity specialization in each district. Results of factor analysis trend commodity crops such as rice, cassava, and maize has a high production level each year, but the commodity sweet potato and peanut production is likely to decline.